FINTECH PEER-TO-PEER LENDING SEBAGAI PELUANG PENINGKATAN UMK DI INDONESIA - Suci Romadhona; Muhammad Zilal Hamzah; Eleonora Sofilda (Media Ekonomi, 2018)
This research was conducted to determine the effect of the factors driving MSEs in making loans to peer-to-peer lending companies. Factors that are considered by MSEs in seeking financial resources through peer-to-peer lending are loan processes, interest rates, loan processing costs, loan amounts, and loan application flexibility. These five factors will then be used as independent variables to see behavioral intentions and the actual use of a peer-to-peer lending platform. This research method uses Structural Equation Modeling (SEM) and WrapPLS 6.0 test equipment. The results of this study found that the loan process had no significant effect on behavioral intentions and other factors had a positive influence and the highest factor affected MSEs borrowing on this platform was the flexibility of loan applications. With the aspirations of MSEs, peer-to-peer lending companies in Indonesia can improve services so that business capital loan transactions increase and advance the economy of MSEs in Indonesia.